A Rare Complication of Biliary Pancreatitis Forming a Radiological Mass Mimicking a Klatskin’s Tumor - Alvina; Aloysius, Mark; Onwuzo, Chidera; Sapkota, Bishnu (Brazilian Journal of Case Reports, 2025)
A Klatskin tumor, a type of cholangiocarcinoma that develops where the right and left hepatic bile ducts join to form the common bile duct. These tumors, first identified by Altemeier et al. in 1957 and later elaborated upon by Klatskin in 1965, typically occur within 2 cm of the hilar confluence and account for 50–70% of all cholangiocarcinomas. It is important to differentiate Klatskin tumours from various benign conditions and other malignant lesions that can mimic both the clinical presentation and radiological appearance, often termed Klatskin-like lesions. There have been multiple reports of hilar strictures initially diagnosed as cholangiocarcinoma and it has been found that 5-15% of these cases ultimately exhibit benign lesions upon final histopathological examination. To our knowledge there is no case of a complication of biliary pancreatitis leading to the formation of a radiological lesion mimicking a Klatskin’s like tumor, being reported in the literature. Therefore, this case report represents the first documented instance of this intriguing occurrence.